2009
DOI: 10.1021/bi900980g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Structure of the Manganese-Responsive Transcriptional Regulator ScaR,

Abstract: The streptococcal coaggregation regulator (ScaR) of Streptococcus gordonii is a manganese-dependent transcriptional regulator. When intracellular manganese concentrations become elevated, ScaR represses transcription of the scaCBA operon, which encodes a manganese uptake transporter. A member of the DtxR/MntR family of metalloregulators, ScaR shares sequence similarity with other family members, and many metal-binding residues are conserved. Here, we show that ScaR is an active dimer, with two dimers binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 54 publications
6
79
1
Order By: Relevance
“…These results revealed similarity to streptococcal coaggregation regulator (ScaR) (PDB ID 3hru) (Z-score, 7.1), iron-dependent regulator (IdeR) (PDB ID 1u8r) (Z-score, 6.7), and diphtheria toxin repressor protein (DtxR) (PDB ID 1c0w) (Z-score, 5.6). These proteins are all part of the metal and DNA-binding protein families that function as transcriptional regulators (61)(62)(63)(64)(65)(66)(67)(68). In addition, these proteins all have three domains: a DNA-binding, a dimerization, and an SH3-like domain (64,69,70), where the structure of FeoA resembles the last domain (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results revealed similarity to streptococcal coaggregation regulator (ScaR) (PDB ID 3hru) (Z-score, 7.1), iron-dependent regulator (IdeR) (PDB ID 1u8r) (Z-score, 6.7), and diphtheria toxin repressor protein (DtxR) (PDB ID 1c0w) (Z-score, 5.6). These proteins are all part of the metal and DNA-binding protein families that function as transcriptional regulators (61)(62)(63)(64)(65)(66)(67)(68). In addition, these proteins all have three domains: a DNA-binding, a dimerization, and an SH3-like domain (64,69,70), where the structure of FeoA resembles the last domain (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5B). The presence of metal ions signals these proteins to transition between the DNA-binding and nonbinding forms (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)73). The SH3-like domains of IdeR and DtxR also play an important role in this conversion apart from sole metal binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ScaR represses the expression of scaCBA in the presence of Mn 2ϩ . Biochemical studies of the S. gordonii and S. pneumoniae ScaR proteins have shown that ScaR is a homodimer and contains two metal-binding sites per protomer (85,86). In S. pneumoniae ScaR, Zn 2ϩ occupies site 1, and although it is required for activation, it keeps ScaR in an inactive state.…”
Section: One-component Systemsmentioning
confidence: 99%
“…The ferric uptake regulator Fur and zinc uptake regulator Zur constitute the majority of the Fur family metalloregulators, being widely distributed in diverse lineages of Bacteria but not Archaea, whereas the manganese-and nickel-specific regulators Mur and Nur were found in only some bacterial lineages (9,10). Manganese-responsive DtxR family regulators were studied in many bacteria, including MntR in Escherichia coli (11), Bacillus subtilis (12), Staphylococcus aureus (13), Corynebacterium diphtheria (14), and C. glutamicum (15,16), ScaR in Streptococcus gordonii (17), and TroR in Treponema pallidum (18), where they mostly control genes for manganese uptake transporters. In contrast, iron-responsive TFs from the DtxR family were found only in Actinobacteria and include two experimentally studied TFs, the diphtheria toxin repressor DtxR in Corynebacterium diphtheriae (19) and the iron-dependent regulator IdeR in Mycobacterium tuberculosis (20,21), which control large networks of genes involved in iron homeostasis and other cellular functions, such as the toxin gene in C. diphtheriae.…”
mentioning
confidence: 99%